2011
DOI: 10.5194/nhess-11-2859-2011
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary analysis for traces of the last state of earthquake generation in preseismic electromagnetic emissions

Abstract: Abstract. Many questions about earthquake (EQ) generation remain standing. Fracture induced electromagnetic (EM) fields allow real-time monitoring of damage evolution in materials during mechanical loading. An improved understanding of the EM precursors has direct implications for the study of EQ generation processes. An important challenge in this direction is to identify an observed anomaly in a recorded EM time series as a pre-seismic one and correspond this to a distinct stage of EQ generation. In previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 108 publications
(169 reference statements)
0
21
0
Order By: Relevance
“…Despite the amount of research and the conflicting related argumentation and analysis e.g. the recent publications [11][12][13][55][56][57][58] and the references therein, the restricted number of detected LF pre-seismic kHz bursts still bounds the analysis and, more or less, confines the predictive power of the kHz radiation. On the other hand, the MHz recordings collected from aboveground antennas, exhibit low EM noise and high predicting ability [6,7,31,54] as proved from more than 15 signals in the MHz range published so far.…”
Section: Hurst Exponent Estimation Through Rescaled-range Analysismentioning
confidence: 99%
“…Despite the amount of research and the conflicting related argumentation and analysis e.g. the recent publications [11][12][13][55][56][57][58] and the references therein, the restricted number of detected LF pre-seismic kHz bursts still bounds the analysis and, more or less, confines the predictive power of the kHz radiation. On the other hand, the MHz recordings collected from aboveground antennas, exhibit low EM noise and high predicting ability [6,7,31,54] as proved from more than 15 signals in the MHz range published so far.…”
Section: Hurst Exponent Estimation Through Rescaled-range Analysismentioning
confidence: 99%
“…First, based on a multidisciplinary statistical analysis, we have shown that the kHz EM time series is characterized by the following crucial symptoms of an extreme phenomenon (Potirakis et al, 2011Eftaxias, 2012, and references therein): (i) high organization or high information content. Tools of information theory, concepts of entropy rooted in the extensive and non-extensive Tsallis statistical mechanics, and measures of complexity have been used in order to identify the aforementioned features (Shannon nblock entropy, Shannon n-block entropy per letter, conditional entropy, entropy of the source, Kolmogorov-Sinai entropy, T entropy, approximate entropy -ApEn, Fisher information, correlation dimension, R/S analysis, detrended fluctuation analysis, fractal dimension, and finally fractal wavelet spectral analysis).…”
Section: Arguments In Terms Of Statistical Analysismentioning
confidence: 99%
“…It is important to note also that some values above 2 can be observed. These are associated with persistency which has been interpreted by some researchers [10][11][12][13]70,71] as the most significant precursory sign of the inevitable phase of the earthquake occurrence. According to other researchers [11,16,17,43,44,[55][56][57][58] the most important sign is the change between anti-persistency and persistency -which can be observed in Figure 3a -whereas the majority of values is well above 1.5 -the case of Figure 4a, as aforementioned.…”
Section: : (I) a Power-law Value Of B = 2 Means That There Is No Corrmentioning
confidence: 98%
“…In addition, the LF emissions of the kHz range have been employed only in few cases (Kozani-Grevena, Athina and L'Aquila earthquakes) as seismic precursors. Despite the great research and argumentation [6,[10][11][12][13]70,71], the few detected signals still restrict the results and set them under scientific debate. Note that, based on several arguments, the investigators of these papers claim that the detected kHz anomalies refer to the inevitable last phase of the earthquake evolution.…”
Section: Seismicity Of the Investigated Time-period (2007-2015)-critementioning
confidence: 99%